Qiyâs dan Istihsân dalam Rasionalitas Usûl al-Sarakhsî - Mawardi, Ahmad Imam (ISLAMICA: Jurnal Studi Keislaman, 2012)
There are two conceptual terms that this paper will try to expose. The first is analogy (qiyâs) and the second is istihsân, an analogyâlike method of extrapolating jurisprudential rules. The paper will try to speak of their relationship in the light of al-SarakhsÃ®âs rationality. In the field of Islamic jurisprudence, the two concepts are often seen as contradicting to one another. The Shafiâite jurists are even of belief that using istihsân is legally forbidden for that would contradict the general rules of Islamic law. The paper assumes that despite general view of the jurists that istihsân is an equivocal method it can nonetheless be fitted into qiyâs. To show that however, the paper would inevitably re-define both qiyâs and istihsân as proposed by al-Sarakhsî. By exploiting the ideas of al-Sarakhsî, the paper hopes that new lights may be shed as far as the richness of Islamic method injurisprudence is concerned.